Delivering gene therapy for mucopolysaccharide diseases - Wood, Shaun R.; Bigger, Brian W. (Frontiers in Molecular Biosciences, 2022)
Mucopolysaccharide diseases are a group of paediatric inherited lysosomal storage diseases that are caused by enzyme deficiencies, leading to a build-up of glycosaminoglycans (GAGs) throughout the body. Patients have severely shortened lifespans with a wide range of symptoms including inflammation, bone and joint, cardiac, respiratory and neurological disease. Current treatment approaches for MPS disorders revolve around two main strategies. Enzyme replacement therapy (ERT) is efficacious in treating somatic symptoms but its effect is limited for neurological functions. Haematopoietic stem cell transplant (HSCT) has the potential to cross the BBB through monocyte trafficking, however delivered enzyme doses limit its use almost exclusively to MPSI Hurler. Gene therapy is an emerging therapeutic strategy for the treatment of MPS disease. In this review, we will discuss the various vectors that are being utilised for gene therapy in MPS as well as some of the most recent gene-editing approaches undergoing pre-clinical and clinical development.